(untitled) (Iraqi Journal of Medical Sciences, 2023)
The communal Myrtus of Linn (Myrtus communis L.) can be defined as one of the most potent medicinal plants in the world is (family: Myrtaceae). The Mediterranean and Middle Eastern regions are home to the common myrtle, Myrtus communis L. The fruit of the myrtle has a distinct flavor and comes in either black or white. It is frequently used to treat a variety of ailments, including gastric ulcers, diarrhea, dysentery, vomiting, rheumatism, bleeding, deep sinusitis, leucorrhoea, and cosmetic issues including hair loss. Wine and cuisine are flavored with the blades, berries, and branches. Due to its high vitamin content, mature fruits were once utilized as a food integrator. It has been demonstrated in numerous studies that the myrtle plant’s various parts contain a variety of bioactive substances. The plant’s fruit and leaves both contain phenolic chemicals and anthocyanin, as well as quercetin, catechin, and myricetin. Numerous biologically active compounds are produced by the plant, including tannins, flavonoids, coumarins, strong oil, essential oils, fibers, carbohydrates, citric acid, malic acid, and antioxidants. The bioactive chemicals found in various myrtle plant sections are regarded to have beneficial benefits on health. According to earlier research, the plant has antioxidant, antibacterial, antidiabetic, anti-inflammatory, anti-ulcerative, anti-diarrheal, analgesic, and hair-growing properties. More human researches are required because it has been shown that the majority of these investigations are conducted on animals. Keywords:Myrtus communis Linn; antioxidant activity, antidiabetic and anti-inflammatory activity, antiulcerative and antidiarrheal activity; analgesic effect and effect on hair growth Citation:Abass HA, Mahmeed BA, Omran ZS. Myrtus Communis Linn and its potential health effects: A review. Iraqi JMS. 2023; 21(1): 118-123. doi: 10.22578/IJMS.21.1.13